PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 022 RIMBO PANJANG KECAMATAN TAMBANG - Suharnis '; Otang Kurniaman; Gustimal Witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Currently, main problem in Education, perticularly in natural science subject at 5th grade of SD Negeri 022 Rimbo Panjang Kecamatan Tambang is Students had low score. This is because their had a problem about comprehension. This condition proof by score of students at mid test got average only 61.5. The percentage of students who reached KKM only 50% from 20 students, and total of students who completed only 10 students. Researcher interested to did experiment in SD Negeri 022 Rimbo Panjang Kecamatan Tambang with implementation of inquiry learning model to increase result of natural science subject of students 5th grade in SD Negeri 022 Rimbo Panjang Kecamatan Tambang. This research is Study Class type that did at students of 5th SD Negeri 022 Rimbo Panjang Kecamatan Tambang. Instrument in this research consist of Teaching administrations based on KTSP or known by Curriculum of 2016. Teaching administrations consist of syllabus, RPP, students work sheets, observation sheets. in Cycle 1 for first meeting got “preety good” Category. The percentage of teacher activity reached 41%. In second meeting also got “preety good” Category. The percentage of teacher activity reached 54%. Meanwhile after cycle 2 be an increased in third meeting with “Good” Category with percentage 66%. In fourth meeting increasing occured with percentage 75% Good Category. Activity who did by students in learning process of natural science subject in cycle 1 for first meeting got the percentage 41% with “preety good” Category. In second meeting got the percentage 58% with “preety good” Category. Meanwhile in third meeting of cycle 2 activity of students increased and got percentage 70% with “good” category. Fourth meeting got percentage 79% with “good” category. Result of lesson Studets in natural science subject at 5th grade had basic score is 50% of amount students, whereas at daily test 1 students who reached KKM become 60% of amount students, and at daily test 2 amount of students who reached KKM increased become 80%. And also in data early average score 61,5 in cycle 1 increased become 67 and at cycle 2 got average score 72,25. Keyword: inquiry learning type, learning outcames IPA